If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 60x + 153 = -9x Reorder the terms: 153 + 60x = -9x Solving 153 + 60x = -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 153 + 60x + 9x = -9x + 9x Combine like terms: 60x + 9x = 69x 153 + 69x = -9x + 9x Combine like terms: -9x + 9x = 0 153 + 69x = 0 Add '-153' to each side of the equation. 153 + -153 + 69x = 0 + -153 Combine like terms: 153 + -153 = 0 0 + 69x = 0 + -153 69x = 0 + -153 Combine like terms: 0 + -153 = -153 69x = -153 Divide each side by '69'. x = -2.217391304 Simplifying x = -2.217391304
| 4.5(x-1)=2.7 | | 9s-10=-82+s | | 40-5x=340-45x | | -23+11x-9x=23 | | 14(x-2)+5=16(x+1)+17 | | (3x+5x+7)+(-5x+14)= | | 10=3.5m | | 2.4m=48 | | 27n=216 | | -30+10x-8x=22 | | 6.4x-3.5x=-87 | | 32x-14=-18 | | 9(3b+2)+3b=116+76 | | 8x-5=7x+8 | | -7x-8x=75 | | 8(a+8)+2a=56+14 | | -3=5y+12 | | -0.5(-12)= | | 0.5(4x+6)=0.3(9x-24) | | 25-4x=13-8x | | -4x-3x-74=38 | | 3x+12=-30-3x | | 2m+10=18 | | 3x+12=-30 | | x^2+6xy+9y^2-1=0 | | (f+9)20=140 | | 12=-2/5(5)+x | | 2q+4=-8 | | 7x^3-32x^2-15x=0 | | 9-(y+6)=9-y+6 | | 15(2y+1)=75 | | 8x-49=3x+56 |